1975
DOI: 10.1002/ccd.1810010204
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Ventricular Performance: A Computer‐Based System for the Analysis of Angiographic Data

Abstract: A computer-based quantitative angiography system for the acquisition and analysis of ventriculographic data has been developed. In addition to the apparatus normally required for angiography and left ventricular pressure recording, a digitizing tablet, PDP 11/20 mini computer, and TV monitor with a hard-copy device is employed. Four modes of operation are currently in use: data acquisition, analysis, mini cine, and data tape editor. Data acquisition facilitates forming a magnetic tape record of the digitized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown that, when used properly, such measurements are reliable and reasonably accurate (3,20,34,35). There is no doubt that MR imaging techniques are more accurate and reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that, when used properly, such measurements are reliable and reasonably accurate (3,20,34,35). There is no doubt that MR imaging techniques are more accurate and reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…In the CAESAR, left ventricular volume (Vmeas) is also calculated by the area-length method, calibrated in ml on the basis of a calibration sphere, and corrected by Heintzen's formula (LV,,, = 0.72 X V, , , , -4.7 ml) [7]. While the users traced the contours on the DCI, an observer recorded the amount of time needed for this manual procedure, as well as the left ventricular segments which required subsequent manual corrections.…”
Section: Discussionmentioning
confidence: 99%